THE ROLE OF GOVERNANCE SUPERVISION ON DELAYS IN AUDIT REPORTS OF COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Rosnita Rosnita (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
The research aims to investigate the effect of corporate governance and audit report lag. The independent variables of this research are audit committee size, audit committee independence, audit committee expertise, audit committee diligence, board size, board independence, and board diligence. With control variables in the form of company size, profitability, gender, and the type of auditor. As well as the dependent variable to be examined is audit report lag. The study used samples from non-financial companies that have annual reports and complete financial reports from 2017 to 2021, namely 2,020 data from 404 companies listed on the Indonesia Stock Exchange (IDX). The collection of samples in this study used a purposive sampling method. The data studied is the company's annual financial statements that have been audited. Data were analyzed using logistic regression analysis, where some of the variables is a dummy variable. The results of the study prove that the variables of audit committee independence, board size, board independence, board diligence, profitability, and type of auditor have a significant positive effect on audit report lay, while the variables of audit committee size, audit committee diligence, and gender have a negative effect but not significant to audit report lag. Meanwhile, other variables such as expertise of the audit committee and firm size have a non-significant positive effect on audit report lag.